Eupator’s Unmarried Sisters. On the Dynastic Struggle in Pontos after the Death of Mithridates V Euergetes - Ballesteros-Pastor, Luis (Anabasis. Studia Classica et Orientalia, 2013)
Plutarch (Lucullus 18) reports about two sisters of Mithridates Eupator who were about forty years old in 71 BC. This age would suggest that these princesses were not the daughters of Mithridates V Euergetes, who had died ca. 122 BC. After the king’s death, therefore, there was some struggle in the court of Sinope. The accounts about the dangers suffered by Eupator during his childhood may reflect aspects of the Iranian education, but, at the same time, these episodes probably echoed plots planned by the regent queen Laodice in order to hinder the prince’s accession to the throne. The queen was probably supported by Iranian nobles of the kingdom. However, the quarrel in the royal palace was not due to an opposition between Iranians and Greeks: it was just a struggle for power.